Structural Plasticity of the Selectivity Filter in Cation Channels - Hendriks, Kitty; Öster, Carl; Lange, Adam (Frontiers in Physiology, 2021)
Ion channels allow for the passage of ions across biological membranes, which is essential for the functioning of a cell. In pore loop channels the selectivity filter is a conserved sequence that forms a constriction with multiple ion binding sites. It is becoming increasingly clear that there are several conformations and dynamic states of the selectivity filter in cation channels. Here we outline specific modes of structural plasticity observed in the selectivity filters of various pore loop channels: disorder, asymmetry and collapse. We summarize the multiple atomic structures with varying selectivity filter conformations as well as asymmetric and more dynamic states that were discovered recently using structural biology, spectroscopic, and computational methods. Overall, we discuss here that structural plasticity within the selectivity filter is a key molecular determinant of ion channel gating behavior.